The INventory of Callous-Unemotional Traits and Antisocial Behavior (INCA) for Young People: Development and Validation in a Community Sample - Morales-Vives, Fabia; Cosi, Sandra; Lorenzo-Seva, Urbano; Vigil-Colet, Andreu (Frontiers in Psychology, 2019)
Callous-unemotional traits are defined as potential markers of psychopathy in children and adolescents. Previous studies with the most widely used instrument designed specifically to assess these traits, the Inventory of Callous-Unemotional Traits (ICU), have shown major methodological problems. For this reason, the purpose of the present study was to develop a valid and reliable test to assess callous-unemotional traits for the adolescent population free of the response biases social desirability (SD) and acquiescence (AC). In order to obtain responses free of these biases, we used SD item markers as well as content balanced items to identify a factor related to SD and AC, so that SD and AC effects can be removed from the individual scores on content factors. As well as the CU traits (unemotional, callousness and uncaring scales), this new questionnaire also contains an additional scale for assessing antisocial behaviours. The test was administered to 719 adolescents between 13 and 19 years old. Exploratory and confirmatory factor analysis yielded the following expected four dimensions with a good fit:. Unemotional, Callousness, Uncaring and Antisocial Behaviour These scales also showed good psychometric properties with good reliability, and convergent, discriminant and criterion validity.